Legal Contemplation Regarding Healthcare and Covid-19 - Bhupinder Singh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Public healthcare and disease prevention is the utmost concerns of the governments around the world. The quality, accountability and accessibility of health infrastructure along with medicines are desired so that the people use these resources at the time of medical emergency. Good health is measured when the mortality rate, malnutrition, huger, pollution and other parameters are low and does not impact upon the individual’s life. The communicable and non-communicable diseases put harmful effect on the health and life the people and COVID-19 which is a pandemic spread all over the world through transmission. The World Health Organisation issued various guidelines for safety and security but it’s a medical emergency like situation and governments of the countries already framed rule and regulations for the prevention/ protection and eliminate the transmission of disease through lockdown. There are number of legal provisions at international and national level for health and medicare as well as implementation of government mandates for protection from corona virus.